Tajikistan - Improving Statistics for Children's Births and Deaths - World Bank (World Bank, 2012)
The Government of Tajikistan has identified improving maternal and child health (MCH) as key priorities in its new Health Sector Strategy for 2010-2020. The Government recognizes that improving MCH outcomes is critical to achieve the Millennium Development Goals (MDG) for maternal and child health over the next four years. Tajikistan's data on most of the MDG indicators for maternal and child health can be improved significantly. The Government's ability to track its progress and to take action to ensure the achievement of its MDGs will be considerably bolstered by access to reliable data on childbirths, child mortality and others factors that affect these outcomes. To improve data reporting, data collection needs to be consistent in its methods and sources, which is currently not the case. As a result, health facilities and national agencies' reports diverge significantly from the results of nationally representative surveys. With this in mind, the study therefore set out to identify the main factors affecting two specific areas of Tajikistan's Health Information System-namely the child birth and death registration system as well as the possible steps to address them. The analysis reveals a number of issues that are key constraints to the further development of the vital statistics system in Tajikistan, particularly in the specific area of registration of births and deaths. Most of these go well beyond the health sector's span and call for broader action by the Government in order to be effectively and comprehensively addressed. The most important is the absence of clear leadership and ownership among the Government agencies for the issues related to accurate vital statistics. In view of this, there are several priority actions that have to be taken over the short to medium term by the Government and its key agencies to improve this situation. The most critical action is to clearly establish one Government agency to undertake the overall coordination, responsibility and ownership on the issue of vital statistics.